2006
DOI: 10.1103/physreve.73.056611
|View full text |Cite
|
Sign up to set email alerts
|

Class of solitary wave solutions of the one-dimensional Gross-Pitaevskii equation

Abstract: We present a large family of exact solitary wave solutions of the one dimensional GrossPitaevskii equation, with time-varying scattering length and gain/loss, in both expulsive and regular parabolic confinement regimes. The consistency condition governing the soliton profiles is shown to map on to a linear Schrödinger eigenvalue problem, thereby enabling one to find analytically the effect of a wide variety of temporal variations in the control parameters, which are experimentally realizable. Corresponding to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(153 citation statements)
references
References 31 publications
2
151
0
Order By: Relevance
“…Focusing our attention on BECs alone, it is well known that the Gross-Pitaevskii (GP) equation governs the evolution of macroscopic wave function at ultra low temperatures [6,9]. In particular, for cigar shaped BECs, it has been shown that the GP equation can be reduced to the 1D variable coefficient NLS equation [10][11][12] iψ t + 1 2 ψ xx + R(t)|ψ| 2 ψ + 1 2 β(t) 2 x 2 ψ = 0,…”
Section: Introductionmentioning
confidence: 99%
“…Focusing our attention on BECs alone, it is well known that the Gross-Pitaevskii (GP) equation governs the evolution of macroscopic wave function at ultra low temperatures [6,9]. In particular, for cigar shaped BECs, it has been shown that the GP equation can be reduced to the 1D variable coefficient NLS equation [10][11][12] iψ t + 1 2 ψ xx + R(t)|ψ| 2 ψ + 1 2 β(t) 2 x 2 ψ = 0,…”
Section: Introductionmentioning
confidence: 99%
“…In addition, if one wants to compare the final results with the experimental results, one has to choose the appropriate time-dependent potential, for further discussions one can see Ref. [15].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors has written the evolution of the condensate wave function, trapped by three-dimensional anisotropic function, and containing the time-dependent potential describing gain or loss effect as [15] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, GP gain equation is of special importance in the field of an atom laser, that is a device which produces an intense coherent beam of atoms by a stimulated process [12,13]. In recent years, GP gain equation (1) has also been studied mathematically by some authors [14,15,16]. GP gain equation can also be used in the theory of optical fibers if the harmonic trap potential is assumed to be zero [15,16].…”
Section: Introductionmentioning
confidence: 99%